2016
DOI: 10.1007/s13277-016-5291-8
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderic acid targeting multiple receptors in cancer: in silico and in vitro study

Abstract: Receptor tyrosine kinases (RTKs) are transmembrane high-affinity surface receptors responsible for cell migration, adhesion, apoptosis, metabolism, and cell proliferation activities in various cancers. Minute aberration in the RTK signaling modulates the downstream signaling pathways that results in cancer. Ganoderic acid is a triterpene isolated from Ganoderma lucidum, which is renowned for its therapeutics effect, especially in cancer. The present study discusses receptor-based molecular docking of insulin r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…G. lucidum modulates the signaling of cancer cells by inhibiting NF-κB nuclear translocation RAS-mitogen-activated protein kinase (MAPK) activation and apoptosis processes. In particular, GA, a triterpene isolated from G. lucidum , strongly inhibits the activation of transmembrane surface receptors (RTKs) [ 49 ], which modulate intracellular downstream signals responsible for cell adhesion, proliferation, migration, apoptosis, and metabolism in various cancer cells. Specifically, 50 isoforms of GA were studied in relation to specific inhibition of RTKs such as insulin receptor (IR), insulin-like growth factor (IGFR), VEGFR1, VEGFR2, and estrogen receptor in liver cancer cells (Figure 4 ).…”
Section: Direct Anticancer Activitymentioning
confidence: 99%
“…G. lucidum modulates the signaling of cancer cells by inhibiting NF-κB nuclear translocation RAS-mitogen-activated protein kinase (MAPK) activation and apoptosis processes. In particular, GA, a triterpene isolated from G. lucidum , strongly inhibits the activation of transmembrane surface receptors (RTKs) [ 49 ], which modulate intracellular downstream signals responsible for cell adhesion, proliferation, migration, apoptosis, and metabolism in various cancer cells. Specifically, 50 isoforms of GA were studied in relation to specific inhibition of RTKs such as insulin receptor (IR), insulin-like growth factor (IGFR), VEGFR1, VEGFR2, and estrogen receptor in liver cancer cells (Figure 4 ).…”
Section: Direct Anticancer Activitymentioning
confidence: 99%
“…Ganoderma products are nowadays consumed worldwide as a health tonic and dietary supplement with its current annual sales over US$2.5 billion (Li et al, ). Ganoderic acids (GAs), a group of highly oxygenated lanostane‐type triterpenoids, are well recognized as a main group of unique bioactive compounds in the medicinal mushroom (Bishop et al, ; Li et al, ; Shiao, ; Tang, Liu, Zhao, Wei, & Zhong, ; Xiao & Zhong, ; Zhong & Xiao, ); and several individual GAs have been reported to possess important biological and pharmacological activities including antitumor, anti‐metastasis, and anti‐HIV effects in both in vitro and in vivo studies (Bishop et al, ; Gill et al, ; Sato, Zhang, Ma, & Hattori, ; Tang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…2003 ;Tang, Liu, Zhao, Wei, & Zhong, 2006;Xiao & Zhong, 2016;Zhong & Xiao, 2009); and several individual GAs have been reported to possess important biological and pharmacological activities including antitumor, anti-metastasis, and anti-HIV effects in both in vitro and in vivo studies (Bishop et al, 2015;Gill et al, 2016;Sato, Zhang, Ma, & Hattori, 2009;Tang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that Ganoderic acids (GA) are the major components of GT [ 14 ] and exhibit extraordinary pharmacological activities, especially anticancer activity, that affect multiple signaling pathways involved in the pathogenesis of ADPKD [ 15 18 ]. Hence, in this study, 12 monomers were isolated from GA, and their anti-cyst activity was assessed using in vitro and in vivo cyst models [ 19 ].…”
Section: Introductionmentioning
confidence: 99%